Bi-directional drones to strengthen healthcare provision: experiences and lessons from Madagascar, Malawi and Senegal. Issue 4 (30th July 2019) - Knoblauch, Astrid M; de la Rosa, Sara; Sherman, Judith; Blauvelt, Carla; Matemba, Charles; Maxim, Luciana; Defawe, Olivier D; Gueye, Abdoulaye; Robertson, Joanie; McKinney, Jesse; Brew, Joe; Paz, Enrique; et al.
Abstract : Drones are increasingly being used globally for the support of healthcare programmes. Madagascar, Malawi and Senegal are among a group of early adopters piloting the use of bi-directional transport drones for health systems in sub-Saharan Africa. This article presents the experiences as well as the strengths, weaknesses, opportunities and threats (SWOT analysis) of these country projects. Methods for addressing regulatory, feasibility, acceptability, and monitoring and evaluation issues are presented to guide future implementations. Main recommendations for governments, implementers, drone providers and funders include (1) developing more reliable technologies, (2) thorough vetting of drone providers' capabilities during the selection process, (3) using and strengthening local capacity, (4) building in-country markets and businesses to maintain drone operations locally, (5) coordinating efforts among all stakeholders under government leadership, (6) implementing and identifying funding for long-term projects beyond pilots, and (7) evaluating impacts via standardised indicators. Sharing experiences and evidence from ongoing projects is needed to advance the use of drones for healthcare.